2007
DOI: 10.1177/1525822x06298588
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying the Personal Network Name Generator

Abstract: Researchers studying personal networks often collect network data using name generators and name interpreters. We argue that when studying social support, multiple name generators ensure that researchers sample from a multidimensional definition of support. However, because administering multiple name generators is time consuming and strains respondent motivation, researchers often use single name generators. We compared network measures obtained from single generators to measures obtained from a six-item mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(79 citation statements)
references
References 39 publications
0
75
0
4
Order By: Relevance
“…The use of multiple name generator questions is deemed appropriate in order to reduce the level of forgetting by the respondent, which is especially appropriate when making use of so-called recall methods (Marsden 2006). Previous research indicated that the use of multiple name generators consistently provide more reliable estimates compared to the use of a single name generator (Marin and Hampton 2007).…”
Section: Appendixmentioning
confidence: 99%
“…The use of multiple name generator questions is deemed appropriate in order to reduce the level of forgetting by the respondent, which is especially appropriate when making use of so-called recall methods (Marsden 2006). Previous research indicated that the use of multiple name generators consistently provide more reliable estimates compared to the use of a single name generator (Marin and Hampton 2007).…”
Section: Appendixmentioning
confidence: 99%
“…On the survey, participants selected up to six Facebook friends to whom they felt close. Respondents were instructed to select ties " … you discuss important matters with, really enjoy socializing with, or anyone else you feel especially close to" (Marin & Hampton, 2007). On average, participants selected 4.4 close friends.…”
Section: Tie Strengthmentioning
confidence: 99%
“…Being a member of a council provides common topics to talk about. Youth councils appear to be a core network (Hampton, Sessions & Ja Her, 2011;Lin, Cook & Burt, 2001;Marin & Hampton 2007) and members see each other as core confidants (Hampton, 2011). This is illustrated by the scenarios described, where members talk about their use of social media and their preference to keep their conversations accessible for members only.…”
Section: Discussionmentioning
confidence: 99%